1985
DOI: 10.1159/000118189
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous EEG Paroxysms in the Rat: Effects of Psychotropic and Alpha-Adrenergic Agents

Abstract: Approximately 20% of Charles River rats which were chronically implanted with brain electrodes for EEG recordings exhibited within half a year of the implantation spontaneous, paroxysmally occurring, steep EEG potentials of high amplitude (spikes and waves) whilst falling asleep. These EEG paroxysms were dose dependently antagonized by the ‘petit mal drugs dipropylacetate, ethosuximide and trimethadione as well as by the anticonvulsant drugs diazepam and nitrazepam. The neuroleptics chlorpromazine, haloperidol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 24 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…observations]. We note that clonidine can enhance S&W also in Sprague-Dawley rats [36], and in general, several investigations are consistent with the con cept that the presynaptic noradrenergic deficit present in Sprague-Dawley GEPR9 and GEPR3 rat brains is un compensated by postsynaptic receptor increments [37][38][39]. In the EEG of the C57B1/6 'tottering' mouse as well, S&W bursts may be observed that are very similar to those of DBA/2J mice and GEPR rats, and in this former mouse strain an elevation in norepinephrine levels within most locus coeruleus projection fields was shown [40] .…”
Section: Discussionmentioning
confidence: 58%
“…observations]. We note that clonidine can enhance S&W also in Sprague-Dawley rats [36], and in general, several investigations are consistent with the con cept that the presynaptic noradrenergic deficit present in Sprague-Dawley GEPR9 and GEPR3 rat brains is un compensated by postsynaptic receptor increments [37][38][39]. In the EEG of the C57B1/6 'tottering' mouse as well, S&W bursts may be observed that are very similar to those of DBA/2J mice and GEPR rats, and in this former mouse strain an elevation in norepinephrine levels within most locus coeruleus projection fields was shown [40] .…”
Section: Discussionmentioning
confidence: 58%
“…Also spike-wave discharges can be noticed in random bred Wistar rats, but the prevalence and incidence of these discharges is much lower compared to age-matched WAG/Rij rats [14]. In two studies it was shown that at an age of six months only 10 or 20% of random bred rats including Wistars show spike-wave discharges [15,31]. It is therefore safe to conclude that Wistar rats quantitatively, differ in the amount of spontaneously occurring spike-wave discharges from WAG/Rij rats.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, spindles arc generated by the caudate nucleus underlying the frontal cortex [5], The dominant frequency of the spin dles seems to be stage-dependent. During DoTr and Tran the power peaks were measured between 10 and 12 Hz, during PAROX between 6 and 9 Hz (spikes and waves; [9]) and between 12 and 18 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…Delta-activity was low. Some rats suffer from spontaneously occurring parox ysmal spike and wave activity in the EEG without mo toric seizures (petit mal [9]). In this study 8 rats with EEG paroxysms were evaluated.…”
Section: Characteristics O F the Power Spectramentioning
confidence: 99%